Characterization of digital systems used in medical X-ray imaging. (November 2022) - Perez, A.M.M.M.; Poletti, M.E.
Abstract: The physical characteristics of two computed radiography (CR) systems, Carestream EHR-M3 and Carestream GP-2 (used in mammography and general radiography, respectively), were assessed at the standard beam conditions RQA-M2 and RQA-5, in the ranges of 9.5–800 μGy and 2.5–70 μGy, respectively. Objective criteria such as response function, modulation transfer function (MTF), normalized noise power spectrum (NNPS) and detective quantum efficiency (DQE) were employed for this evaluation. A careful image system noise analysis through component decomposition was performed in order to determine the quantum limited exposure range for each system. Both CR systems showed a logarithmic response in the tested air kerma range (R 2 > 0.99). Spatial frequencies for 50% and 10% MTF were 2.0 mm −1 and 4.9 mm −1 for EHR-M3 mammography system and 1.1 mm −1 and 3.5 mm −1 for general radiography system GP-2. The mammography system EHR-M3 was quantum limited for the entire air kerma range evaluated, while GP-2 general radiography system was quantum noise limited for a range of 2.5–30 μGy. NNPS increased as kerma decreased for both systems. DQE increased with decreasing kerma for both systems. A quantitative technical characterization of digital systems was achieved for a variety of air kerma values, in the mammography and general radiography energy ranges. Highlights: Physical characterization of CR systems used in mammography and general radiography. Both CR systems showed a logarithmic response in the tested air kerma range (R 2 > 0.99). Quantum limited exposure range determined in an air kerma interval of 2.5–800 μGy. DQE increased with decreasing kerma for mammography and general radiography detectors.